NORMA SANKSI DAN TEORI PIDANA INDONESIA - Zaidan, M Ali (Jurnal Yuridis, 2014)
Norms and sanctions in the criminal law are duumvirates nature. Interplay between the two. Norm without sanctions would lead to paralysis; sanctions that are not otherwise supported by the norms that will either lead to arbitrariness. Indonesian Penal Theory needs to build and developed with reference to the development of leading edge science and doctrine developed by the developed contries. Without losing the distinctive characteristics of the Indonesian Penal Theory. Guardiantship of a criminal theory that should be developed models in order to guide the prevention of crime and treatment of offenders.